Sound production by the West Australian dhufish (Glaucosoma hebraicum) - Parsons, Miles; Longbottom, Simon; Lewis, Paul; McCauley, Robert; Fairclough, David (Australian Acoustical Society, 2013)
Biological examinations of Glaucosomatid fish species have suggested that they could produce sound via swimbladder vibration, using “sonic” muscles. However, there have been few reported instances of it in the family. West Australian dhufish (Glaucosoma hebraicum) is an iconic teleost, endemic to Western Australia. Dissection of G. hebraicum in this study identified the presence of “sonic” muscle pairs in immature and sexually mature individuals. The muscle tissue originates in the otic region of the skull with its insertion at the anterior of the swimbladder. Recordings of sounds were acquired from two male G. hebraicum, at a range of 1m, during capture. Calls comprised 1 to 14 swimbladder pulses with spectral peak frequency of 154±45 Hz (n=67 calls) and 3 dB bandwidth of 110±50 Hz. The mean of all call maximum source levels was 126 dB re 1 µPa at 1m with the highest level at 137 dB re1 µPa at 1m. The confirmation of sound production by G. hebraicum and the acoustic characteristics of those sounds could be used to gain a better understanding of its ecology and, particularly, whether the production of sound is associated with specific behaviors, such as reproduction.